META-HEURISTIC CLONAL SELECTION ALGORITHM FOR OPTIMIZATION OF FOREST PLANNING - Araújo Júnior, Carlos Alberto; Mendes, João Batista; Cabacinha, Christian Dias; Assis, Adriana Leandra de; Matos, Lisandra Maria Alves; Leite, Helio Garcia (Revista árvore, 2017)
ABSTRACT It is important to evaluate the application of new technologies in the field of computational science to forest science. The goal of this study was to test a different kind of metaheuristic, namely Clonal Selection Algorithm, in a forest planning problem. In this problem, the total management area is 4.210 ha that is distributed in 120 stands in ages between 1 and 6 years and site indexes of 22 m to 31 m. The problem was modeled considering the maximization of the net present value subject to the constraints: annual harvested volume between 140,000 m3 and 160,000 m3, harvest ages equal to 5, 6 or 7 years, and the impossibility of division of the management unity at harvest time. Different settings for Clonal Selection Algorithm were evaluated to include: varying selection, cloning, hypermutation, and replacement rates beyond the size of the initial population. A generation value equal to 100 was considered as a stopping criteria and 30 repetitions were performed for each setting. The results were compared to those obtained from integer linear programming and linear programming. The integer linear programming, considered to be the best solution, was obtained after 1 hour of processing. The best setting for Clonal Selection Algorithm was 80 individuals in the initial population and selection. Cloning, hypermutation, and replacement rates equal to 0.20, 0.80, 0.20 and 0.50, respectively, were found. The results obtained by Clonal Selection Algorithm were 1.69% better than the integer linear programming and 4.35% worse than the linear programming. It is possible to conclude that the presented metaheuristic can be used in the resolution of forest scheduling problems. RESUMO Dada a importância de se avaliar novas tecnologias para otimização do planejamento florestal, este trabalho objetivou introduzir a metaheurística Clonal Selection Algorithm na resolução de um problema de ordenamento da produção florestal. Considerou-se uma área manejada de tamanho igual a 4.210 ha, contendo 120 talhões com idades entre 1 e 6 anos e índice de sítio variando entre 22 m e 31 m. O problema foi modelado com o objetivo de se maximizar o valor presente líquido global do empreendimento e considerou como restrições uma demanda anual entre 140.000m3 e 160.000 m3, colheita apenas nas idades de 5, 6 e 7 anos e a imposição de não fracionamento dos talhões no momento do corte. Foram avaliados diferentes configurações da metaheurística Clonal Selection Algorithm, variando-se as taxas de seleção, clonagem, hipermutação e substituição, além do tamanho da população inicial. Considerou-se como critério de parada uma quantidade de gerações igual a 100 e para cada parametrização avaliou-se 30 repetições. Os resultados foram comparados com aqueles obtidos utilizando-se programação linear e programação linear inteira. Para a programação inteira considerou-se a melhor solução após 1 hora de processamento. A melhor configuração foi a que considerou 80 células na população inicial, taxas de seleção, clonagem, hipermutação e substituição iguais a 0,20, 0,80, 0,20 e 0,50, respectivamente. Os resultados apresentados pela metaheurística Clonal Selection Algorithm foram 1,69% superiores à programação linear inteira e 4,35% inferior a programação linear. Conclui-se que a metaheurística apresentada pode ser utilizada para resolução de problemas de ordenamento florestal.